Corporations through the Looking Glasses: For an Ethnography of the Global - Bougleux, Elena (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
During a three years investigation in the Research & Development Department of a multinational corporation in Bangalore, I investigated the interplay between processes of knowledge and technology transfer, massive investments in infrastructures, and the modified political and social equilibrium in the receiving local context. The patterns of global expansion drawn by the US-based corporation in India retrace the trajectories of British colonial power. The corporation is described as an actor capable of shaping not only the economic present scenario, but also triggering processes of historical identification and claim. The corporation major transformative actions affect the imaginaries of work, increase salaries and productivity, produce provisional empowerment of local workforce; but they also bring about diffused social resistance and indirectly foster strategies of appropriation. Two examples of “appropriated technology” are described: sustainable and low cost products, designed by the Indian researches in the Bangalore R&D to meet the needs of rural areas and disadvantaged villages, represent the material translation of a local demands into the corporate terms of technology. At the same time, they are presented by the corporation in its world wide campaigns as innovations developed to respond to green requirements and new environmental standards. This ambiguity and intentional misunderstanding constitutes the fabric of the ongoing complex relations between the corporation and the “emerging” contexts of its expansion.